Moderate hypofractionation for prostate cancer: A user's guide. Issue 2 (16th January 2018) - Pryor, David I; Turner, Sandra L; Tai, Keen Hun; Tang, Colin; Sasso, Giuseppe; Dreosti, Marcus; Woo, Henry H; Wilton, Lee; Martin, Jarad M
Summary: Three large randomised controlled trials have been published in the last year demonstrating the non‐inferiority of moderate hypofractionation compared to conventional fractionation for localised prostate cancer with respect to both disease control and late toxicity at 5 years. Furthermore, no clinically significant differences in patient‐reported outcomes have emerged. More mature follow‐up data are now also available from phase 2 studies confirming that moderate hypofractionation is associated with low rates of significant toxicity at 10 years. Moving forward it is likely that appropriate patient selection, integration of androgen deprivation and attention to optimising technique will play a more important role than modest differences in dose‐fractionation schedules. Here we briefly review the evidence, discuss issues of patient selection and provide an approach to implementing moderately hypofractionated radiation therapy for prostate cancer in clinical practice.